1996
DOI: 10.1007/bf00011302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ammonium and nitrate application on the NO and N2O emission out of different soils

Abstract: The effect of nitrate and ammonium application (0, 50, 100 and 150 mg N kg -1 soil) was studied in an incubation experiment. Four Belgian soils, selected for different soil characteristics, were used. The application of both nitrate and ammonium caused an increase of the NO and N20 emission. The NO production from nitrate and ammonium was found to be of the same order of magnitude. At low pH the NO production was found to be highest from nitrate, at higher pH values the production was found to be higher from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…Soils with a pH of 7-8 are supposed to produce higher amounts of N 2 (Simek and Cooper, 2002) but revealed an order of magnitude larger N 2 O emissions than soils with a pH between 4 and 6 (Vermoesen et al, 1996). A soil pH of 6.7-7.1 measured at our limestone site restricts selfdecomposition of HNO 2 and might, therefore, be responsible for small NO fluxes (Van Cleemput and Samater, 1996).…”
Section: No X Fluxesmentioning
confidence: 75%
“…Soils with a pH of 7-8 are supposed to produce higher amounts of N 2 (Simek and Cooper, 2002) but revealed an order of magnitude larger N 2 O emissions than soils with a pH between 4 and 6 (Vermoesen et al, 1996). A soil pH of 6.7-7.1 measured at our limestone site restricts selfdecomposition of HNO 2 and might, therefore, be responsible for small NO fluxes (Van Cleemput and Samater, 1996).…”
Section: No X Fluxesmentioning
confidence: 75%
“…Hadas et al (1996) suggested that extensive emissions of N 2 O instantly following application of organic amendments might result from rapid growth of zymogenous bacteria in response to addition of the high-energy organics present in the amendments. Many studies have found that NO 3 -is sequentially reduced to NO, N 2 O, and N 2 , and that more N 2 O is emitted from N fertilized soils (Mosier 1994;Vermoesen et al 1996;Drury et al 1998). Kaiser et al (1998) found, in a 3-yr study, that a linear increase in N fertilization rate (three application rates: 0, 105, 210 kg N ha -1 ) did not result in a linear increase in N 2 O emissions.…”
Section: N 2 O Emissionsmentioning
confidence: 97%
“…Nitrogen fertilization increases N 2 O emission from soil by providing additional available N (Mosier 1994;Vermoesen et al 1996;Drury et al 1998;MacKenzie et al 1998). Previous studies have found that the application of liquid pig manure, liquid pig manure plus wheat straw compost and yard waste compost resulted in a decrease in the availability of inorganic N as a result of N loss through denitrification and/or N immobilization.…”
Section: Mots Clésmentioning
confidence: 99%
“…Baggs et al 2010 oraz Vermoesen et al (1996) podaj¹, ¿e w glebach wapnowanych N 2 O powstaje g³ównie w wyniku nitryfikacji. W naszej ocenie emisja N 2 O z gleb wapnowanych utrzymuje siê jednak na wzglêd-nie niskim poziomie.…”
Section: Wstêpunclassified
“…W porównaniu do nawozów amonowych, nawo¿enie saletrzane zwiêksza emisjê N 2 O, ale tylko z gleb zakwaszonych, w których dominuj¹cym procesem jest denitryfikacja. Na glebach o wy¿szej wartooeci pH i o mniejszej wilgotnooeci wiêksza emisja N 2 O ma miejsce po zastosowaniu nawozów amonowych (Liu et al 2007, Vermoesen et al 1996. Wed³ug Zalewskiego (2013) w Polsce obserwuje siê w ostatnich latach wzrost zu¿ycia mocznika kosztem zmniejszenia zu¿ycia saletry amonowej.…”
Section: Wstêpunclassified